PENGEMBANGAN MAJALAH BERBASIS PROJECT BASED LEARNING TERINTEGRASI PROFIL PELAJAR PANCASILA MATERI KEKAYAAN BUDAYA INDONESIA UNTUK SISWA KELAS IV SEKOLAH DASAR - Sekar Nutty Wijayanti; Muflikhul Khaq; Rintis Rizkia Pangestika (Jurnal Binagogik, 2024)
The problem in this research is based on the problem of the absence of accompanying teaching materials, the absence of project-based learning media, the lack of application of the Pancasila student profile character, the lack of understanding of the material riches of Indonesian culture. This research aims to: 1) Produce a product in the form of an Integrated Project Based Learning Magazine based on Pancasila Student Profiles Material on Indonesian Cultural Wealth for Class IV Elementary School Students which is in accordance with development procedures. 2) Knowing the feasibility of the Integrated Project Based Learning Magazine based on the Pancasila Student Profile. The type of research used in this research is research and development using the Borg and Gall model which consists of 10 stages. The research subjects were students in class IV of SD Muhammadiyah 1 Purworejo for the 2022/2023 academic year with a total of 34 students. Data was collected using observation, interviews and questionnaires. The results of research into the development of an Integrated Project Based Learning Magazine, Pancasila Student Profile Material on Indonesian Cultural Wealth are: 1) this research produces a product in the form of an Integrated Project Based Learning Magazine, Pancasila Student Profile Material on Indonesian Cultural Wealth for Class Students IV Elementary School, 2) Product validity results obtained an average score of 96% in the very valid category, practicality results obtained an average score of 86% in the very practical category. Based on this study, it can be concluded that the Integrated Project Based Learning Magazine, Pancasila Student Profile, Indonesian Cultural Wealth Material for Class IV Elementary School Students is suitable for use as learning media or accompanying teaching materials in elementary schools.